From India to Aruba: Insight into Teaching and Cultural Approaches in India and the Dutch Caribbeans Medical Education System - Arnaw Kishore (Journal of Clinical and Diagnostic Research)
As an academician, I recently transitioned from Assistant Professor of Microbiology and Molecular laboratory incharge in India to Assistant Professor of Microbiology and Immunology and Secretary Research at a medical school in the Dutch Caribbean. This provides a unique perspective on medical education in two distinctly different regions. I currently work at Xavier University School of Medicine (XUSOM), in Oranjestad, the capital of Aruba one of the ABC islands (Aruba, Bonaire and Curaçao) in the lesser Antilles [1].